Pre-service english teachers`challenges in communicative language teaching approach - Guaita Saquinga, Cinthia Noemi (2023)
The Communicative Language Teaching (CLT) methodology allows students to learn the language in real contexts and develop their communicative skills in the classroom. The main objective was to determine pre-service teachers' opinions about the challenges in Communicative Language Teaching implementation. A descriptive qualitative methodology was used. The participants were 18 students at the eighth level of the Technical University of Cotopaxi. They answered a structured interview of 32 questions and descriptive statistics were used to analyze the data obtained. The results showed that in the category related to educational policies, the lack of coherence and the lack of relationship between didactic materials and MINEDUC interrupts an adequate implementation of the approach, in the category focused on (CLT) implementation, the large number of students per classroom, indiscipline, inadequate infrastructure and preferences for learning grammar instead of communicative skills have created barriers so that a successful implementation process cannot take place and in the category focused on prior knowledge about (CLT), it was shown that pre-service English teachers prefer to teach only grammatical structures rather than communicative competences in English classes due to the lack of knowledge and they do not use pair/ group work to develop communication skills. In conclusion, it can be stated that trainee English teachers faced several challenges in applying the methodology (CLT) because they did not have enough knowledge about the approach.